The Influence Of Occupational Health, Safety And Work Environment On Performance Through Risk Management At Pip Semarang - Ahmad Faisal; Vitrianna Sulistyaningrum; April Gunawan Malau; Ali Muktar Sitompul; Bambang Sumali; Imam Fahrudin (Dinasti Publisher, 2024)
This study aims to analyze the impact of occupational health and safety (OHS) and work environment on employee performance through risk management at PIP Semarang. The main issue identified is how OHS and the work environment influence employee performance both directly and through risk management. The population of the study includes all employees of PIP Semarang, with a sample of 100 civil servants selected randomly. The research employs a quantitative method using questionnaires for data collection. Data analysis is performed using SMART PLS to evaluate the relationships between variables. The findings reveal that both OHS and the work environment have a significant direct positive impact on risk management, and also directly affect employee performance. Additionally, risk management plays a significant mediating role in the relationship between OHS, work environment, and performance. The study concludes that improvements in OHS and the work environment can enhance employee performance both directly and through risk management. Recommendations for PIP Semarang include enhancing the work environment and OHS practices, and improving coordination in risk management to boost overall employee performance.